Urgensi Perpustakaan Islam Digital dalam Menyediakan Literatur Keislaman bagi Muslim Milenial - Machsun Rifauddin; Arfin Nurma Halida (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Islamic literature in Indonesia is rapidly transitioning from print to digital, and an Islamic digital library may be crucial to meeting society's more complex needs in the information age. The purpose of this article is to describe the movement in Islamic literature from printed to digital in Indonesia, as well as the importance of digital Islamic libraries for the millennial Muslim. Researchers utilise literature studies to acquire data from published books, journals, and scientific publications. The data analysis followed the Miles concept of data reduction, data display, and conclusion drawing / verification. While triangulation is used to validate the data. The results show a strategic relationship between information technology, the information society,d digital libraries. The development of digital Islamic libraries in the information age is driven by the increasing need for Islamic literature among millennial Muslims and their tendency to access Islamic literature through the internet. Islamic libraries are essential for digitizing and disseminating digital Islamic literature relevant to millennial Muslims. Additionally, access must be granted as a means of monitoring Islamic information.